No place for a lady : tales of adventurous women travellers - Hodgson, Barbara, 1955- (Vancouver : Greystone Books, 2002)
Presents accounts of world travel by women over the past three hundred years.
Includes bibliographical references (pages 207-211).
Keywords: Women travelers; Voyages and travels; Voyages and travels; Women travelers